Ayanna01
Ayanna01
10-04-2015
Mathematics
contestada
(-y+5•3)+7.2y-9)=6.2y+n
Respuesta :
alybsinger
alybsinger
10-04-2015
(-y+5x3)+(7.2y-9)=6.2y+n
(-y+15)+(7.2y-9)=6.2y+n
since you're adding the two parentheses, you don't need to have them there
-y+15+7.2y-9=6.2y+n
7.2y-y +15-9 =6.2y+n
6.2y + 6 =6.2y+n
6.2y - 6.2y -n = -6
-n=-6
n=6
Answer Link
VER TODAS LAS RESPUESTAS ( 21+ )
Otras preguntas
What is the complement of the angle 178 degrees and 100 degrees
Suppose you invest $580 at 10% compounded continuously , write an exponential function to model the amount in your investment account ?
could you tell me what is a genre?
Is it possible to make CD without plastic? why or why not?
What it is the quadratic formula ?
write quadratic equation whose roots are 4 and -3 and whose leading coefficient is 5 use the letter X to represent the variable ? =0
why is citizen participation essential to the preservation of the us political system
Can someone show me how to solve this? A boat took 5 hours to travel 60km up a river, against the current. The return trip took 3 hours. Find the speed of the b
the amount of postage placed on a first class letter depends on the weight of the letter .
Express the set in roster form.{x|x is a natural number multiple of 5}